A Turn-On Fluorescent Chemosensor for Cyanide Ion Detection in Real Water Samples - Shi, Qing; Wu, Shou-Ting; Shen, Lingyi; Zhou, Tao; Xu, Hong; Wang, Zhi-Yong; Yang, Xian-Jiong; Huang, Ya-Li; Zhang, Qi-Long (Frontiers in Chemistry, 2022)
A new simple colorimetric and fluorescent probe with aggregation-induced emission (AIE) characteristic has been designed and synthesized. The probe 5-(4-(diphenylamine)phenyl) thiophen-2-formaldehyde W exhibited a turn-on fluorescent response to cyanide ion (CN-), which induces distinct naked-eye color changes. Probe W exhibited excellent selectivity and sensitivity for the detection of CN- over a wide pH range (4-11) and in the presence of common interferents. The linear detection of CN- over the concentration range of 4.00 μM to 38.00 µM (R2=0.9916) was monitored by UV-Vis absorption spectrometry (UV-Vis), and the detection limit was found to be 0.48 µM. The linear detection of CN- over the concentration range of 8.00 μM to 38.00 µM was examined by fluorescence spectrophotometry (R2=0.99086), and the detection limit was found to be 68.00 nM. The sensing mechanisms were confirmed by 1H NMR spectroscopic titrations, X-ray crystallographic analysis, and HRMS. Importantly, probe W could be used to detect and quantify CN- in real water samples with high precision and good accuracy over the range 100.17% 100.86% in artificial lake water and 100.54% 101.64% in running water by UV-Vis absorption spectrometry, and over the range 99.42% 100.71% in artificial lake water and 100.59% 101.17% in running water by fluorescence spectrophotometry. Importantly, this work provides a simple and effective approach which uses an economically cheap and uncomplicated synthetic route for the selective, sensitive and quantitative detection of CN- ions in systems relevant to the environment and health.